2018
DOI: 10.1002/adma.201705615
|View full text |Cite
|
Sign up to set email alerts
|

Designer Shape Anisotropy on Transition‐Metal‐Dichalcogenide Nanosheets

Abstract: MoS and generally speaking, the wide family of transition-metal dichalcogenides represents a solid nanotechnology platform on which to engineer a wealth of new and outperforming applications involving 2D materials. An even richer flexibility can be gained by extrinsically inducing an in-plane shape anisotropy of the nanosheets. Here, the synthesis of anisotropic MoS nanosheets is proposed as a prototypical example in this respect starting from a highly conformal chemical vapor deposition on prepatterend substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 94 publications
0
46
0
1
Order By: Relevance
“…MoS 2 films which were deposited on a rippled SiO 2 substrate were shown to exhibit Raman anisotropy. 146 Patterning on prepatterned substrates can enable the study of emerging materials properties associated with strain and shape anisotropy 147 ; however, fabricating electrical or optoelectronic devices from such methods may prove difficult. A lithographic technique to create free-standing metal (e.g., Mo, W, Sn) structures was demonstrated, which can then be sulfurized via a CVD process.…”
Section: Emerging Nanopattering and Lithographic Techniques Lateral Hmentioning
confidence: 99%
“…MoS 2 films which were deposited on a rippled SiO 2 substrate were shown to exhibit Raman anisotropy. 146 Patterning on prepatterned substrates can enable the study of emerging materials properties associated with strain and shape anisotropy 147 ; however, fabricating electrical or optoelectronic devices from such methods may prove difficult. A lithographic technique to create free-standing metal (e.g., Mo, W, Sn) structures was demonstrated, which can then be sulfurized via a CVD process.…”
Section: Emerging Nanopattering and Lithographic Techniques Lateral Hmentioning
confidence: 99%
“…Chemical Vapor Deposition telah lama berkembang, seperti literature yang telah kami dapatakan yaitu dari tahun 2000-2018, sudah banyak sekali yang dihasilkan oleh Chemical Vapor Deposition. (61)(62)(63)(64)(65)(66)(67)…”
Section: Pendahuluanunclassified
“…Recently, many studies have been reported on the strain effect of 2D layered materials [10][11][12]. This effect has been proved that the optical band gap can be tuned by up to several hundred meV/% in atomically thin TMDs by local strain [13].…”
Section: Introductionmentioning
confidence: 98%